Social media and best practice: the consumer brand relationship - Maw, Yan Aung (The IIE, 2016)
The consumer-brand relationship is an essential part in the success of a brand, and therefore brands need to be both aware of this as well as leverage the relationship to its full potential. The study will identify the most important aspects in maintaining and developing this relationship over social media, digital platforms where consumers and brands interact with each other, in a South African context. Past research indicates that social media is growing in popularity, and therefore communication needs to be differentiated to increase engagement with the brand and ultimately, brand equity (Yan, 2011). Brand equity is the level of familiarity a consumer has with a brand, therefore the brand wishes to achieve a high brand equity. This study has made use of a collective case study to explore the relationship between the consumer and brands that use social media. The results of the study have identified what is important to the consumer and also compared to brand manager responses, via triangulation. This includes Facebook, the social media platform being the most used both by consumers and by brands. Brands highlighted the importance of having an online presence, in order for brands to easily communicate with consumers, and vice versa. User generated content needs to be used carefully, as also with responding to negative remarks. This study will propose a best practice recommendations to follow to build brand equity online, and in addition, suggest a strategy to ‘activate’ the results of the research paper in a creative way.
Theses
Keywords: Consumer-brand relationship; Social media; Brand equity; Facebook